The analysis of contributing factors to septic death in Pakkred Hospital - Hanlumyuang, Gingkan (Journal of Preventive Medicine Association of Thailand, 2020)
Sepsis is a serious condition and major cause of worldwide hospital mortality. It was also one of the major causes of deaths in Pakkred Hospital in the year 2018. This study was conducted to analyse contributing factors to septic death in Pakkred Hospital, while aiming to develop more effective care in order to reduce the overall mortality rate. The investigation was based on the evidences appeared between October 2018 and March 2019. The total number of 36 patients, consisting of 23 survivors and 13 non-survivors with community acquired sepsis was accounted for. The factors that were associated with septic death were organ dysfunctions of equal to or greater than 3 organs (survivor 17.39%, non-survivor 92.30%, P=0.000) especially in respiratory system (survivor 30.43%, non-survivor 76.92%, P=0.007) peripheral tissue/metabolic acidosis (survivor 8.69%, non-survivor 69.23%, P=0.000) and hepatic system (survivor 4.34%, non-survivor 30.76%, P=0.028). Intravenous fluid therapy was considered adequate and appropriate in both groups. On the contrary, the delay in the administration of intravenous antibiotics was found in both groups. This information is key imperative to the planning and development of the care for sepsis patients in Pakkred hospital in the future.